Analysis Of The Impact Of Islamic Religious Education On Cognitive Development Of Junior-Age Children - Syafruddin Syafruddin; Lukman Ismail; Ifan Rizky Kurniyanto; Muhammad Syahid; Endang Supriatna (IJGIE (International Journal of Graduate of Islamic Education), 2023)
The purpose of this study was to determine the impact of Islamic religious education on the cognitive development of middle school-aged children. The method that researchers use is qualitative research with a type of literature study. The library research steps to be carried out in this study include: a) preparing equipment; b) compiling a framework; c) managing time; d) reading and making research notes. In this study, data sources were obtained from relevant literature, such as books, journals, or scientific articles related to the selected topic. The data collection technique used in this library research is to find data about things or variables in the form of notes, books, papers or articles, journals, and so on. The research instrument used by researchers is a check-list list of research material classifications based on the focus of the study, writing schemes and maps, and research note formats. The data analysis technique used in this research is content analysis. The results of this study show that Islamic religious education teachers have a very important role in the cognitive development of children of middle school age. This is because middle school-age children in their cognitive development begin to be able to think abstractly, think critically, and have the ability to solve more complex problems. Reflective thinking ability. Creative thinking ability. For this reason, religious education teachers in schools who are developing students' cognitive skills need to use several strategies, namely providing examples to students, habituating positive activities every day at school, using creative teaching methods, giving advice, and finally, giving punishment.